Memórias de um economista: Schacht e a Alemanha nos anos 1920 - Sartório, Sarah Goncalves Patrocinio (2019)
This Master Thesis is about Germany in the 1920s. Initially the theater of operations of World War I (1914-1918) will be presented, mentioning the human and material losses and emphasizing some of the main battles that composed this great conflict, as the battles of Marne and Somme. After the end of the first war, the new territorial reorganization of Europe will be shown, with the disintegration of empires and the emergence of new countries. Next, war reparations are discussed, as well as the immense obstacles on the way to the full restoration of the world economic order. The perceptions and memoirs of the German economist, Hjalmar Schacht, about the given period are set forth below. Schacht was the Secretary of Currency, president of the Reichsbank, and minister of economics in the between the WWs. He was the guardian of the German currency, which demanded of him rather than control monetary policy, but also strive intransigently for the end of war reparations.